A Quantitative Methodology for Determining Relevant Geographic Markets in Higher Transportation Cost Industries. (December 2018) - De Stefano, Martino; Tsai, Joanna
The U.S. Department of Justice/Federal Trade Commission Horizontal Merger Guidelines describes the hypothetical monopolist test (HMT) and significant and nontransitory increase in price (SSNIP) as tools to define antitrust markets. However, the discussion leaves some ambiguities with regards to the implementation of such tools. In this article, we present a methodology for quantitatively delineating geographic markets that is consistent with the Guidelines. In particular, for geographic markets that are based on the locations of customers, the market boundaries encompass the region into which sales are made from the merging parties' plants, and competitors in the market are firms that sell to customers in the specified region. We use two approaches to identify the competitive reach of a plant—one based on actual shipping distances, which reflect the areas where the plant actually sells; and the other based on distances at which the plant's product can be shipped profitably, which reflect all areas where the plant can potentially compete for customers. These distances are used to "draw circles" around plants to identify areas where one merging party plant's competitive reach overlaps with the reach of another plant belonging to the merging partner, thus identifying the overlap customers. For each identified overlap customer area, the HMT is implemented using the critical loss analysis following a SSNIP by the hypothetical monopolist. We explain how to calculate the critical loss as well as the likely actual loss from the SSNIP.